Performance evaluation of asphalt mixture incorporating Polyethylene Terephthalate - Nasir, Nabil Irfan; Wan Azahar, Wan Nur Aifa; Kasim, Norhidayu; Basri, Nur Khairiyah; Ramli, Ahmad Bukhari; Kamaruzaman, Nur Atikah (Springer, 2025)
Environmental and economic benefits have led to an increase in the use of waste materials like Polyethylene Terephthalate (PET) in asphalt binder manufacture. Pavement distress occurs when the asphalt surface layer does not retain its original shape, due to demands placed on the material by traffic, temperature changes, and sun exposure. Road construction includes producing asphalt pavements, which usually involve the use of bituminous binders. This study included a comparative analysis and laboratory tests on the qualities of PET asphalt mixes versus traditional asphalt mixtures. The tests performed included sieve analysis, Los Angeles Abrasion Value (LAAV) testing, Aggregate Crushing Value (ACV) testing, penetration testing, soft ening point testing, and the Marshall Stability test. The experiment used PEN 60/ 70 bitumen grade with five different PET mix percentages (0, 1, 3, 5, and 7%) by weight of the bitumen. The results showed that adding PET to bitumen enhances its engineering properties and the performance of asphalt mixtures. The study found that the optimal PET content in bitumen is 7% by replacement weight, as it offers higher stability and stiffness compared to the control sample